How well do we need to control blood glucose before discharging DKA patients? A retrospective cohort study - Chi Tang; Ruth Kouides (Greater Baltimore Medical Center, 2014)
Purpose: To determine the ideal length of stay and glycemic control after resolution of acidosis in patients hospitalized for diabetic ketoacidosis, in order to reduce 30-day readmission. We hypothesized that both discharging patients within 24 hours of acidosis resolution and hyperglycemia at discharge are associated with higher probability of readmission. Methods: We examined data from 208 consecutive patients hospitalized for diabetic ketoacidosis. Logistic regression was performed adjusting for age, blood glucose (BG) level at presentation, prior hospitalization within 30 days, season of current hospitalization, and length of hospital stay. Results: Higher BG at discharge is associated with lower probability of readmission (odds ratio, 0.990; 95% CI, 0.983-0.996; P=0.002). Higher average BG over the 24 hours prior to discharge is also associated with lower readmission rate (odds ratio, 0.991; 95% CI, 0.982-1.000; P=0.044). The direction of the association remains the same even after these predictive variables are converted to categorical variables. In addition, discharge within 24 hours of acidosis resolution is not inferior to discharge after 24 hours of normalized BG (odds ratio, 0.431; 95% CI, 0.083-2.252; P=0.318). Conclusion: Neither discharging patients within 24 hours of acidosis resolution nor hyperglycemia at discharge is associated with higher readmission rate. Randomized prospective studies are needed to confirm or refute our study.